THE INFLUENCE OF ENVIRONMENT ON THE MAJOR CHARACTER IN TOREY HAYDEN'S ONE CHILD: A BEHAVIORIST APPROACH - WIDIYASTUTIK , ERLI TRI (2007)
This study attempts to explore the influence of environment to change behavior of the major characters. The objective of the research is to analyze the novel based on its structural elements and analyze the major character based on behaviorist approach. This research belongs to qualitative research, which employs textual data. Textual data are taken from two sources, namely the novel itself as primary data source and the other materials, which are related to the study as secondary data source. The result of this study is as follows: Firstly, the structural elements of the novel present a unity. It appears in the exposition, complication climax and resolution of the story. Secondly, behaviorist analysis shows that someone's behavior can be influenced by environment such as; family, peers, education and community. Environments can give good or bad personality to someone.